The Market Reaction to the Disclosure of Supervisory Actions: Implications for Bank Transparency - Jordan, John S.; Peek, Joe; Rosengren, Eric S. (Journal of Financial Intermediation, 2000)
We examine the stock market reaction to announcements of formal supervisory actions. We find that the variation in the quality and timeliness of disclosure by U.S. banks explains much of the variation in the market's reactions. We also find that these announcements can cause spillover effects. However, rather than representing contagion, these spillover effects are consistent with enhanced transparency. Only banks in the same region as the announcing bank, with similar exposures, are affected. Thus, enhanced disclosure can improve the allocation of resources in the banking system. Journal of Economic Literature Classification Numbers: G21, G28.